Contrasting patterns of MAAs accumulation in two populations of the copepod Boeckella gracilipes - Garcia, Patricia Elizabeth (2014)
The bio-accumulation of mycosporine-like amino acids (MAAs) is common in planktonic copepods that inhabit environments exposed to high levels of solar radiation. MAAs accumulation in copepods can be affected both by extrinsic (environmental) and intrinsic factors (local adaptation, genotype, etc.). Laboratory experiments were performed to study the bio-accumulation of MAAs in two geographically-isolated populations of Boeckella gracilipes from a mountain and a piedmont lake of North Patagonia. We performed two series of 10-day incubations of B. gracilipes from the different lakes applying two radiation conditions (PAR + UVR and darkness), at five different temperatures (5 to 20 °C) and providing a MAA-free flagellate as food. We assumed that differences in final MAAs concentrations between copepod populations should be exclusively due to environmental factors, and that any difference in the patterns of MAAs accumulation should exclusively arise from differences in MAAs concentration at the time of collection. MAAs concentration was three fold higher in B. gracilipes from Lake Verde than in copepods from the Lake Morenito. The MAAs suite was dominated (∼90%) by a combination of porphyra-334 and mycosporine-glycine in copepods from Lake Verde, and porphyra-334 and MAA-332 in those from Lake Morenito. Two exclusive MAA compounds were identified, mycosporine-glycine in copepods from Lake Verde and shinorine in the copepod population from Lake Morenito. Laboratory experiments showed that: (i) exposure to PAR + UVR stimulated the accumulation of MAAs in both copepod populations; (ii) temperature affected the response of MAAs and, remarkably, low temperatures stimulated MAAs accumulation even in dark incubations, (iii) the response to radiation and temperature in MAAs accumulation was more pronounced in the population with low initial MAAs than in the population with high initial MAAs concentrations. The differences in intrinsic factors between B. gracilipes populations, such as local adaptation to contrasting UV and temperature scenarios, among others, appear to play an important role in determining levels and patterns of MAAs accumulation in B. gracilipes.